2016
DOI: 10.3390/s16111888
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Analysis of Ochratoxin A in Beverage Samples

Abstract: This manuscript describes the use of a portable and low cost fluorescence setup to quantify the concentration of ochratoxin A (OTA) in beverage samples using an in-house developed system and different color models. It is reported that OTA is naturally fluorescent, for that reason an ultraviolet light at 365 nm was used to excite the samples and a Complementary Metal Oxide Semiconductor (CMOS) sensor was used to get a photograph of the OTA under excitation conditions, which is controlled by an executable interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This could be attributable to the color space applied. It has been previously reported that RGB space is inherently difficult for humans to comprehend because it is not related to the natural way we perceive colors 24 . In terms of measurement, the difference in relevance of instrument parameters probably be attributed to the different light resources, color models, and resolution fitted with the two instruments.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributable to the color space applied. It has been previously reported that RGB space is inherently difficult for humans to comprehend because it is not related to the natural way we perceive colors 24 . In terms of measurement, the difference in relevance of instrument parameters probably be attributed to the different light resources, color models, and resolution fitted with the two instruments.…”
Section: Discussionmentioning
confidence: 99%
“…CIELab coordinates: To determine the CIELab coordinates, we followed the methodology of the Commission Internationale de l’Eclairage [ 35 ], which have been used by several authors [ 36 , 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Considering that the obtained images are true-color images, it is possible to represent them as 3D matrixes associated with red, green, and blue components [37,38]. The key steps followed for the EE acquisition and elaboration of the regions RGB images are illustrated in the right side of Figure 4.…”
Section: Image Acquisitionmentioning
confidence: 99%